2018
DOI: 10.1080/02650533.2018.1503162
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of children’s outcomes in a residential special school

Abstract: for their thoughtful guidance and many helpful suggestions. We would also like to extend our sincere thanks to the staff of the MBS-who gave their time to collect data, meet with researchers, and contribute to the final text-and to all the pupils, parents and carers who are represented in this report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Four studies reported the efficacy of frameworks of provision (Castro, Grande, and Palikara, 2019; Gutman, Vorhaus, Burrows, et al., 2018; Rees, Tully, and Ferguson, 2017; Stelmaszczyk, 2018). The risk elements related to lack of detail of the researcher's relationship with participants and of the recruitment strategy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies reported the efficacy of frameworks of provision (Castro, Grande, and Palikara, 2019; Gutman, Vorhaus, Burrows, et al., 2018; Rees, Tully, and Ferguson, 2017; Stelmaszczyk, 2018). The risk elements related to lack of detail of the researcher's relationship with participants and of the recruitment strategy.…”
Section: Resultsmentioning
confidence: 99%
“…One study produced overall low‐risk and good‐quality evidence for practice (Castro, et al., 2019), yet improved rigour could have been achieved by collating evidence beyond a single city's local authorities. One study showed risk of other bias as it was funded by the school from which the sample was taken (Gutman, et al., 2018). However, the results of the framework evidence were positive with moderate to large effect sizes and could be influential for other organisations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The children go to school on site and the support for learning consistently takes into account their social and emotional needs. Teaching plays a key part in the therapeutic milieu and pupils make as much progress as would be expected of children in mainstream schools (Gutman, et al., 2018). The school has had an ‘outstanding’ inspection (Ofsted) rating since 2004.…”
Section: The Research Studymentioning
confidence: 99%
“…The qualitative research study based at the University of East London was commissioned by MBS as a complement to University College, London Institute of Education's quantitative research study, also discussed in this special issue (Gutman, Vorhaus, Burrows & Onions, 2018). Whereas the Institute of Education's study focussed on outcomes, the UEL study considered process.…”
Section: Researching the Mulberry Bush Schoolmentioning
confidence: 99%